Targeting Epstein‐Barr Virus dUTPase, an Immunomodulatory Protein Using Antiviral, Anti‐Inflammatory, and Neuroprotective Phytochemicals. Issue 9 (5th September 2022) - Tiwari, Deeksha; Murmu, Sneha; Indari, Omkar; Chandra Jha, Hem; Kumar, Sunil
Abstract: Although primary infection of Epstein‐Barr virus is generally non‐lethal, viral reactivation is often associated with fatal outcomes. Regardless, there is no FDA‐approved treatment available for this omnipresent viral infection. The current investigation targets viral maintenance and reactivation by inhibiting the functioning of viral deoxyuridine‐triphosphatase ( dUTPase ) using phytochemicals. The EBV‐ dUTPase is essential for maintaining nucleotide balance and thus, plays a vital role in the viral replication cycle. Additionally, the protein has shown neuroinflammatory effects on the host. To selectively target the protein and possibly alter its activity, we utilized a virtual screening approach and screened 45 phytochemicals reported to have antiviral, anti‐inflammatory, and neuroprotective properties. The analysis revealed several phytochemicals bound to the target protein with high affinity. In‐silico ADMET and Lipinski's rule analysis predicted favorable druggability of Dehydroevodiamine (DHE) among all the phytochemicals. Further, we corroborated our findings by molecular dynamic simulation and binding affinity estimation. Our outcomes ascertained a stable binding of DHE to EBV‐ dUTPase primarily through electrostatic interactions. We identified that the protein‐ligand binding involves the region around His71, previously reported as a potent drug target site. Conclusively, the phytochemical DHE showed a promising future as a drug development candidate against EBV‐dUTPase. Abstract :